2013
DOI: 10.1074/jbc.m113.469882
|View full text |Cite
|
Sign up to set email alerts
|

The Lhs1/GRP170 Chaperones Facilitate the Endoplasmic Reticulum-associated Degradation of the Epithelial Sodium Channel

Abstract: Background:The epithelial sodium channel (ENaC) is a substrate for the endoplasmic reticulum associated degradation (ERAD) quality control system. Results: The chaperone Lhs1/GRP170 selects the nonglycosylated form of the ␣ subunit for ERAD. Conclusion: This study is the first to show a role for Lhs1/GRP170 in ERAD substrate selection. Significance: Mutations in ENaC are associated with human disease; therefore, Lhs1/GRP170, as a modulator of ENaC expression, may be a target for new therapeutic agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
61
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(75 citation statements)
references
References 114 publications
(145 reference statements)
12
61
1
Order By: Relevance
“…Their data indicated that Hsp40 proteins, independently of Hsp70, might select substrates for ERAD, and that ENaC required unique molecular chaperones for ERAD. They also determined that the chaperone Lhs1/GRP170 (also known as HYOU1) selects the nonglycosylated form of the α-ENaC for ERAD (Buck et al, 2013). Our studies on the ENaC regulation by derlin-1 provide more evidence for ENaC as a substrate for an ERAD quality control system and contribute additional information regarding the pathways of ENaC degradation.…”
Section: Discussionmentioning
confidence: 67%
“…Their data indicated that Hsp40 proteins, independently of Hsp70, might select substrates for ERAD, and that ENaC required unique molecular chaperones for ERAD. They also determined that the chaperone Lhs1/GRP170 (also known as HYOU1) selects the nonglycosylated form of the α-ENaC for ERAD (Buck et al, 2013). Our studies on the ENaC regulation by derlin-1 provide more evidence for ENaC as a substrate for an ERAD quality control system and contribute additional information regarding the pathways of ENaC degradation.…”
Section: Discussionmentioning
confidence: 67%
“…For example, in yeast, the ER lumen-resident heat shock protein (Hsp)70-related Lhs1 selectively targets the ␣-subunit for ER-associated degradation but does not affect the degrada- tion of the ␤-or ␥-subunit (9). Its mammalian homolog, Grp170, also enhances ␣-subunit turnover in human embryonic kidney cells (9). In contrast, luminal Hsp40s enhance the degradation of all three subunits in yeast (8).…”
Section: Discussionmentioning
confidence: 99%
“…Biochemical and structural analyses of the yeast Sil1-Kar2p complex (42) indicate that Sil1 binding to ADP-Kar2p triggers a conformational change in Kar2p that releases ADP; whether this binding reaction is sufficient to induce substrate release from Kar2p, or requires subsequent ATP binding, is not clear. Note that deletion of SIL1 (21) but not LHS1 (39) resulted in a moderate ERAD phenotype, suggesting that Sil1 may exert a potential role in ERAD in yeast.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Grp170's holdase but not NEF activity was implicated in ERAD in mammalian cells (39). In contrast, in part because it is not an ATPase, Sil1's NEF activity likely operates differently from that of Grp170.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation